Study of leucine-rich alpha-2-glycoprotein-1 marker serum level in cases of malignant epithelial ovarian tumors - Agameia, Abd Elfatah; Swelem, Rania Shafik; Sokkary, Hossam Hassan El; Elsayed, Ghada Shehata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The aim of this study was to compare the level of LRG1 in epithelial ovarian cancer (EOC) cases with benign ovarian masses and to evaluate results in relation to CA125. Methods: An observational prospective controlled study was done on 70 patients admitted to El Shatby Maternity University Hospital, Oncology department categorized as follows: study group (group I) included 35 patients, with epithelial ovarian malignancy confirmed by histopathological examination and control group (group Il) included 35 patients with benign ovarian tumors confirmed by histopathological examination. Determination of Serum LRGI level by using enzyme-linked immuno sorbent assay with CA125 tumor marker analysis were done for all cases of both groups. Results: As regard comparison between the two studied groups according to CA125 and LRGI. CA125 in group I ranged from 14.90 to 4600 with a mean value 856.73±1104.03, in group II ranged from 7.45 to 523 with a mean value of 51.97±86.14. LRGI in group I ranged from 62.46 to 653.98 with a mean value of 130.86±119.78, in group Il ranged from 47.73 to 261.78 with a mean value of 77.35±38.75. There was statistically significant difference between the two studied groups regarding CA125 and LRGI (p≤0.05). Conclusions: LRG1 can be used as promising tumor marker to diagnose epithelial malignant ovarian cancer with or without CA125 tumor marker as it was significantly higher in epithelial ovarian cancer patients.